2021
DOI: 10.1177/02654075211059444
|View full text |Cite
|
Sign up to set email alerts
|

The importance of attachment to fathers in Latinx mental health

Abstract: The impact of attachment to fathers on mental health in Latinx communities is understudied and not fully understood, though extant research focusing on maternal attachment forms a solid base of knowledge regarding the importance of attachment (to mothers) on mental health. The broad aim of this study was to examine the importance of paternal attachment in relation to maternal attachment on mental health in Latinx young adults. The current study used two large, young adult samples: one collected in Latin Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Tentatively, it appears that insecure attachment with fathers can be compensated for, to some extent, by the cultural value of familismo and that no such association exists for maternal attachment. This finding, while preliminary, adds to a new literature base regarding differential associations of paternal and maternal attachment in relation to Latinx young adult outcomes (Venta et al, 2021).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Tentatively, it appears that insecure attachment with fathers can be compensated for, to some extent, by the cultural value of familismo and that no such association exists for maternal attachment. This finding, while preliminary, adds to a new literature base regarding differential associations of paternal and maternal attachment in relation to Latinx young adult outcomes (Venta et al, 2021).…”
Section: Discussionmentioning
confidence: 51%
“…The IPPA has also been translated for use in Spanish with satisfactory psychometrics (Delgado et al, 2016; Gallarin & Alonso-Arbiol, 2013). In line with IPPA instructions and prior studies, all participants were instructed to answer parental attachment items about their biological mother and father, even if not their current guardian (Venta et al, 2021). In this study, we used the IPPA mother attachment (Cronbach’s alpha = .96) and father attachment total scores (Cronbach’s alpha = .96) in initial analyses.…”
Section: Methodsmentioning
confidence: 99%
“…While the majority of attachment research has historically focused on the significance of maternal attachment, it is worth discussing research equally emphasizing the importance of paternal attachment security on mental health outcomes (Agerup et al, 2015; Murray & Murray, 2010; Wong et al, 2020), including among Latinx groups. Indeed, prior research has found greater paternal attachment security to be associated with fewer mental health difficulties, even after controlling for the effects of maternal attachment in Central American migrant groups (Venta et al, 2022). Maternal and paternal attachment relationships have also been shown to differ among Latinx groups due to effects of cultural factors, such as gender dynamics (Cabrera & Bradley, 2012; Updegraff et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several researchers have examined the key role of fathers in children’s growth, in particular with regard to matters such as gender equality, individual mental health, children’s early academic success, less truancy, the development of children’s autonomy and moral system, etc., ( Baker et al, 2018 ; Papaleontiou-Louca and Al Omari, 2020 ; Grau et al, 2022 ; Venta et al, 2022 ; Waqar et al, 2022 ). There have also been studies that emphasize the importance of fathers to children’s growth from the perspective of the father’s absence.…”
Section: Introductionmentioning
confidence: 99%